Using Institutional Ethnography to Explicate the Everyday Realities of Nurses' Work in Labor and Delivery. (November 2022) - Kelly, Paula; Quance, Maggie; Snow, Nicole; Porr, Caroline
Fetal health surveillance is a significant everyday work responsibility for labor and delivery nurses. Here, nursing care is increasingly focused on technological interventions, particularly with the use of continuous electronic fetal monitoring. Using Institutional Ethnography, we explored how nurses conduct this work and uncovered the ruling relations coordinating how nurses "do" fetal health surveillance. Analysis revealed how these powerful ruling relations associated with the biomedical and medical-legal discourses coordinated nurses' fetal monitoring work. Forms requiring documentation of biophysical data caused nurses to focus on technological interventions with much less attention given to holistic and supportive care measures. In doing so, nurses inadvertently activated and participated in these powerful ruling discourses. The practice of ensuring the safe birth of the baby through advances in technological surveillance and medical interventions took priority over well-established approaches to holistic nursing care.